Real Issue or Propaganda? Students’ Perspectives on Post Truth Phenomenon in Films - Adzhani, Shabrina An; Ntamwana, Simon (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2025)
The development of information technology has led an era called post truth, when a particular viewpoint is published, accepted as true, and causes other alternative truths to be rejected. It is important for digital citizen to be aware of the existence of such phenomena. This research aims at revealing the perspective of university students semester 6 at English Letters program, UIN Raden Mas Said Surakarta on post truth phenomenon emerging though social media as reflected in two films, Missing and Don’t Look Up. Using reader response approach and McIntire’s theory about post truth, the finding shows that students can generally notice post truth phenomenon in the society and are able to analyse how post truth are circulated. From the last steps of the research, it can be seen that more than half of the students demonstrated a critical and neutral stance, while the rest showed indifference, arguing that they did not know the person involved in the news. Meanwhile, most students showed greater concern and critical thinking when responding to the global issue presented in Don’t Look Up. This indicates that, in general, students demonstrated the necessary attitude—being critical and evaluative of the narratives circulating in the digital platforms.